MALIGNANT MELANOMA OF THE SMALL BOWEL WITH UNKNOWN PRIMARY: A CASE REPORT - Guraya, Salman Yousuf; Naami, Muhammad Al; Tuwaijri, Talal Al; Arafah, Maha Muhammad Irfan (Journal of Ayub Medical College Abbottabad, 2007)
Primary small bowel tumours are rare. However, alongwith stomach it is the most frequent site for metastatic tumours, malignant melanoma being the commo nest tumour. The prevalence of malignant melanoma in the gastrointestinal tract without any evidence of a primary lesion in the skin or any other site is extremely rare. Keywords: Malignant melanoma, Small bowel metastasis, S 100 protein